Reproductive biology of two macrourid fish, Nezumia aequalis and Coelorinchus mediterraneus, inhabiting the NW Mediterranean continental margin (400-2000m) - Fernandez-Arcaya, U.; Ramirez-Llodra, E.; Rotllant, G.; Recasens, L.; Murua, H.; Quaggio-Grassiotto, I.; Company, J. B. (Elsevier, 2013)
Nezumia aequalis and Coelorinchus mediterraneus are abundant species on the upper and lower continental slopes, respectively, in the Mediterranean Sea. A study on the reproductive strategy of the two species was conducted on the Catalan margin (NW Mediterranean). The reproductive cycle of both species was investigated using visual analyses of gonads and histological screening. The shallower species, N. aequalis, showed continuous reproduction with a peak of spawning females in winter months. In contrast, the deeper-living species, C. mediterraneus, showed semi-continuous reproduction with a regression period during the spring. Juveniles of N. aequalis were present in all seasons, but most abundant in the spring. Only two juveniles of C. mediterraneus were found. Both species had asynchronous oocyte development. The average fecundity of N. aequalis was 10,630 oocytes per individual, lower than known for the same species in the Atlantic Ocean. The fecundity of C. mediterraneus was measured for the first time in this study, with an average of 7693 oocytes per individual. Males of both species appear to have semi-cystic spermatogenesis. © 2013 Elsevier Ltd.
Keywords: Deep sea; Fecundity; Macrourid fish; NW Mediterranean; Reproduction; Spermatogenesis; Fish; continental margin; deep sea; fecundity; fish; regression; reproductive biology; reproductive cycle; reproductive strategy; spawning; winter; Atlantic Ocean; Catalonia; Mediterranean Sea; Spain; Coelorinchus; Macrouridae; Nezumia aequalis